Case report: Sarcomatoid urothelial carcinoma of the renal pelvis masquerading as a renal abscess - Chu, Yaru; Ning, Hao; Yin, Ke; Chen, Tong; Wu, Haihu; Wang, Delin; Liu, Feifan; Zhao, Zhenlin; Lv, Jiaju (Frontiers in Oncology, 2023)
Sarcomatoid urothelial carcinoma is a rare and highly aggressive malignant tumour of the urinary tract epithelium.When SUC of the renal pelvis masquerades as a renal abscess, its diagnosis can be a challenge due to the lack of any specific clinical symptoms and imaging findings. We report a patient with sarcomatoid urothelial carcinoma of the renal pelvis presenting as a renal abscess. Repeated anti-inflammatory treatment was ineffective, and exfoliative cytology from the nephrostomy drainage fluid suggested cancerous cells, so that radical surgery was performed to avoid a missed diagnosis. In addition we systematically overview all cases of SUCs of the renal pelvis published after the year 2000, discussing and summarising their clinical presentation, causes, diagnosis and treatment, in order to provide a reference for their clinical management.